Photostories - Gomez, Ricardo (Qualitative and Quantitative Methods in Libraries; Vol 9 No 1 (2020): March 2020 Issue, 2020)
In this paper we discuss the use of Photostories, a participatory visual research method to explore information practices of marginalized and vulnerable communities. Photostories is a method at the intersection of participatory and non-participatory visual methods, drawing from both Photovoice and Photo Elicitation. Photovoice uses participatory photography to empower participants as part of a research process, and Photo Elicitation inserts images into the process of conducting interviews. Though sometimes used interchangeably, Photovoice and Photo Elicitation are different: Photovoice draws from the power of participatory methods to empower participants and their communities through participatory creation of images. Photo Elicitation draws from the power of using images to elicit conversation and meaning as part of the interview process.  Our proposed method, Photostories, builds on the power of participatory photography with participant-generated images as part of the research process and the power of Photo Elicitation techniques that introduce images into the research interview for added insight, perspective and depth. By combining these methods, Photostories offers novel insight and meaning that is hard to obtain using only images or only interviews. We describe our uses of Photostories in Library and Information Science (LIS), where visual methods are not widely used, and invite other researchers to use Photostories and other visual research methods in LIS.